2018
DOI: 10.1002/ets2.12226
|View full text |Cite
|
Sign up to set email alerts
|

Writing Processes in Short Written Responses to Questions Probing Prior Knowledge

Abstract: The purpose of the report is to explore some of the mechanisms involved in the writing process. In particular, we examine students' process data (keystroke log analysis) to uncover how students approach a knowledge‐telling task using 2 different task types. In the first task, students were asked to list as many words as possible related to a particular topic (word listing). In a second task, students were asked to write to a specific prompt that was designed to elicit their background knowledge of a topic usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For example, time spent pausing between bursts, and where pausing occurs, can predict text quality [8]. Other measures of fluency, like typing speed and total time on task, are strongly related to final scores [3]. Sentence-level planning can be indicated by the length of pauses between sentences, while broader planning can be measured by the length of the initial pause before writing [4].…”
Section: Related Workmentioning
confidence: 99%
“…For example, time spent pausing between bursts, and where pausing occurs, can predict text quality [8]. Other measures of fluency, like typing speed and total time on task, are strongly related to final scores [3]. Sentence-level planning can be indicated by the length of pauses between sentences, while broader planning can be measured by the length of the initial pause before writing [4].…”
Section: Related Workmentioning
confidence: 99%
“…ETS has been conducting research on the student writing process using keystroke logging software that captures the sequence and duration of typing actions when a student completes an essay as part of a test (Almond et al, 2012;Deane, 2014;Deane, O'Reilly, et al, 2018;Deane, Roth, et al, 2018;Guo et al, 2019;Sinharay et al, 2019;Zhang et al, 2016;Zhang et al, 2017;Zhang et al, 2019;. The longer texts captured in essay responses should allow more precise measurement of typing dynamics than those resulting from typing passwords.…”
mentioning
confidence: 99%
“…Over the past three decades, a significant amount of studies has demonstrated how writing in small groups or dyads can be beneficial for both developing writing proficiency and for content learning (Rojas-Drummond, et al, 2008;Donahue & Lillis, 2014;Klein & Boscolo 2016;Van Steendam, 2016). And whereas studies on cognitive processes of writers use stimulated recall interviews, thinking aloud procedures and, more recently, keystroke logging (Deane et al, 2018;von Koss Torkildsen et al, 2016) and eye-tracking software (Hacker et al, 2017), studies on collaborative writing focus primarily on the interaction between the participants. Co-writing a text evokes the participants to articulate their thinking processes aloud when they are in consultation with each other about the decisions they have to make as writers.…”
Section: The Sociocultural Context Of Writing Togethermentioning
confidence: 99%
“…Sociocultural environments thus influence the choice of writing strategies, since writing expertise grows through the internalization of generally accepted strategies and procedures for addressing writing problems, which are shared within a community of practice (Deane et al, 2018). Rojas-Drummond, et al (2017) employ the term dialogic literacy, which refers to the interplay between talk, reading and writing.…”
Section: To Collaborative Writing As Literacy Practicesmentioning
confidence: 99%
See 1 more Smart Citation